1969
DOI: 10.2135/cropsci1969.0011183x000900040021x
|View full text |Cite
|
Sign up to set email alerts
|

Components of Test Weight in Soft Wheat1

Abstract: Kernel density, a component of test weight, is not associated with variety when considering Eastern soft wheats Triticum aestivum L. em Thell. (aestivum group), but seems to be related to environment. Air spaces within the grain appear to be a major factor in determining kernel density.Packing efficiency (the percent of bulk volume occupied by grain), the second component of test weight, is associated with variety. Grain shape and surface characteristics such as humping, dorsal or lateral depressions, and wrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 0 publications
5
28
0
Order By: Relevance
“…This correlation may be explained by the fact that the presence of a hull leads to differences in, for example, density, grain shape and surface characteristics. 11,13,15 Starch content and fraction F4 were found to be negatively correlated for the barley samples examined in this study. This means that the barley samples with a high proportion of large grains (High amylose Glacier and SW 906129) had a lower content of starch than the other barley samples, which may be due to a restricted starch synthesis in these cultivars.…”
Section: Principal Component Analysismentioning
confidence: 65%
“…This correlation may be explained by the fact that the presence of a hull leads to differences in, for example, density, grain shape and surface characteristics. 11,13,15 Starch content and fraction F4 were found to be negatively correlated for the barley samples examined in this study. This means that the barley samples with a high proportion of large grains (High amylose Glacier and SW 906129) had a lower content of starch than the other barley samples, which may be due to a restricted starch synthesis in these cultivars.…”
Section: Principal Component Analysismentioning
confidence: 65%
“…But PRO and TKW were not associated, thus suggesting that some component besides PRO, which also influences kernel density, created the association between DF and TKW. Others have reported similar phenotypic correlations between kernel density and PRO, but not between kernel density and TKW (Yamazaki and Briggle 1969;Schuler et al 1995).…”
Section: Resultsmentioning
confidence: 87%
“…197 1). Other studies have suggested that variation in TW is primarily related to differences in WID, kernel thickness, LEN to WID ratio and kernel packing efficiency (Shuey 1960;Merkle et al 1969;, while some have reported low to no association between kernel morphological traits and TW (Yamazaki and Briggle 1969;Schuler et ul. 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Yamazki and Briggle (1969) reported that grain shape is associated with packing efficiency while the environment where the crop is grown mostly affects kernel density [36]. Budak (2000) also confirmed that Kernel shriveling due to drought stress during grain filling period of wheat results in decreasing test weight and grain yield [37].…”
Section: Debre Zeit Akakimentioning
confidence: 99%